Intangible Cultural Heritage: Significance and Stakes - BRAKNI , Abd-El-Baki; Djabri , Nabil (Journal of Ecohumanism, 2025)
Intangible cultural heritage plays a significant role in cultural sociology, representing practices, expressions, knowledge, and skills passed from one generation to another within a particular community or society. It encompasses oral traditions, performing arts, social practices, rituals, and traditional craftsmanship. Through this research paper titled "Intangible Cultural Heritage: Meaning and Challenges, we aim to define intangible cultural heritage and examine the challenges associated with its preservation.